Keterampilan Public Speaking Untuk Meningkatkan Hubungan Kemitraan Dengan Lembaga Nasional dan Internasional dalam Bidang Industri Kerajinan - Melly Ridaryanthi (Jurnal Abdi Masyarakat (JAM), 2025)
Public Speaking is one of the skills required to be able to disseminate information, educate, as well as the running of business which is not acquired by every individual. However, public speaking is necessary in running a business, including SME. Therefore, public speaking workshop and seminar is important and relevant to conduct. Dewan Kerajinan Nasional Daerah (Dekranasda) as the facilitator need to for SMEs, craft, and creative economy in Tangerang Selatan is required to have public speaking skills to support the achievement of the vision and mission of Tangerang Selatan; to develop the competitive and reliable human resources, enhance the functional infrastructure, construct a livable city, develop the innovation based for people’s economy, and enhancing the good governance based on the advancement of information technology.